Political economy of media: An income-expense analysis of state aids to Iranian newspapers (2021)
Iranian newspapers have traditionally relied on state aids and public budget to survive. The dependency has still lingered amid a change of policy that has affected the newspapers’ financial status. This article invokes the available data on governmental support to examine the political economy of newspapers in Iran during the two decades of 1990s and 2000s. The data were collected from official releases by the Iranian Ministry of Culture and Islamic Guidance as well as several nonconfidential internal bulletins of the newspaper organizations. Having applied an income-expense analysis, the paper explains the government’s role in newspaper economics and discusses the policy of repurposing the existing subsidies.